Identification Of Biomarkers For Colorectal Cancer From Malaysian Patients - Yeoh, Lay Chin (2010)
Colorectal cancer (CRC) is on the rise. However, biomarkers for indication of CRC progression is still lacking despite several advances in proteomic and microarray tools. This study aims to identify potential biomarkers for the diagnosis of CRC among Malaysian patients. In this study, sequential extraction was first performed using Tris buffer followed by TLB buffer in order to reduce the complexity of the CRC proteome. The tissues used were surgical resections of normal mucosa and cancerous tissues from 26 CRC patients. The extracted proteins were separated by 2D gel electrophoresis. The differentially expressed protein spots were then mapped for further protein identification by the use of liquid chromatography tandem mass spectrometry (LC-MS/MS). We have identified 37 hydrophilic proteins in the Tris extracts and 24 hydrophobic proteins in the thiourea lysis buffer (TLB) extracts from the samples collected. Leukocyte elastase inhibitor (LEI) and 60 kDa heat shock protein (HSP60) were the potential biomarkers for CRC analyzed from the Tris extracts whereas triosephosphate isomerase (TPI) and annexin A3 were the potential biomarkers for CRC analyzed from the TLB extracts. Moreover, LEI was the potential biomarker for CRC patients at stage III in combination with either moderately differentiated adenocarcinoma (MDA), well differentiated adenocarcinoma (WDA) or lymph node metastasis CRC.